Mengembangkan Ekonomi Masyarakat Melalui UMKM Pengrajin Mebel dengan Sistem Jual Beli Online di Era Covid 19 di Desa Sindangmekar - Achmad Otong Busthomi; Minchatul Hasna Asy’ari; Darrotul Jannah (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2023)
DEVELOPING THE COMMUNITY'S ECONOMY THROUGH MSMES FURNITURE CRAFTSMEN WITH AN ONLINE BUYING AND SELLING SYSTEM IN THE COVID 19 ERA IN SINDANGMEKAR VILLAGE. Micro, Small, and Medium Enterprises (MSMEs) play a vital role in developing the Indonesian economy since they contribute significantly to economic growth. The government will continue to work to foster the development of MSMEs in order to improve economic growth and maximize MSMEs' potential at both the national and village levels. Sindangmekar village has high potential in MSME, one of which is the many people of Sindangmekar village who have opened businesses as furniture craftsmen. Sindangmekar village craftsmen still don't understand how to sell their business products with a digital marketing system, because digital marketing has an important role in marketing a business product because it has a wide enough reach to make it easier for the public to find out what handicraft products are being sold. Because KKN students are helping to teach and realize the economy, especially in furniture making so that it can move into the digital world and be more widely known by all people in Indonesia. This study employs a descriptive qualitative research design, with data collected through observation and the interview method.